2003
DOI: 10.1177/070674370304800509
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects Associated with Physical Restraint

Abstract: Research is needed to provide clinicians with data on the risk factors and adverse effects associated with restraint use, as well as data on procedures that will lead to reduced use. Research is needed to determine what individual risk factors and combinations thereof contribute to injury and death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
216
0
17

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(234 citation statements)
references
References 64 publications
1
216
0
17
Order By: Relevance
“…This includes "therapeutic holding," which has been repudiated as being harmful. 26 During the past 20 years, much research has demonstrated the effectiveness of alternative measures, commonly called "positive behavioral supports," to change behavior. 25 Pediatricians and others who could use additional information about the problems that occur from the use of aversive procedures or restraints can easily get this guidance from the Web sites of organizations such as the Association for the Severely Handicapped (www.tash.org/ IRR/resolutions/res02aversive.htm) and the Autism National Committee (www.Autcom.org/restraints.html).…”
Section: Causal Factorsmentioning
confidence: 99%
“…This includes "therapeutic holding," which has been repudiated as being harmful. 26 During the past 20 years, much research has demonstrated the effectiveness of alternative measures, commonly called "positive behavioral supports," to change behavior. 25 Pediatricians and others who could use additional information about the problems that occur from the use of aversive procedures or restraints can easily get this guidance from the Web sites of organizations such as the Association for the Severely Handicapped (www.tash.org/ IRR/resolutions/res02aversive.htm) and the Autism National Committee (www.Autcom.org/restraints.html).…”
Section: Causal Factorsmentioning
confidence: 99%
“…Still, there are reports on unwanted effects such as prolonged admittance, pressure sores, psychological traumas, and even death [11,[13][14][15][16][17]. Executing coercion and restraint is also stressful for the health-care personal.…”
Section: Introductionmentioning
confidence: 99%
“…This includes an increased chance of physical injury and death among patients as well as staff injury (Evans, Wood, & Lambert, 2003;Rakhmutaullina, Taub, & Jacob, 2013), and both patients and staff report trauma associated with the use of these containment measures (Frueh et al, 2005;Mohr, Petti, & Mohr, 2003;Robins, Sauvageot, Cusack, Suffoletta-Maierle, & Frueh, 2005;Sokol, 2010). Furthermore, the use of these measures raises ethical issues relating to patient rights and dignity, and runs contrary to recovery-oriented mental health care (Chang, Grant, Luther, & Beck, 2014;Mohr, 2010).…”
Section: Introductionmentioning
confidence: 99%